DECISION SUPPORT FOR POST-ACUTE CARE REFERRALS: DEVELOPMENT AND IMPLEMENTATION - Bowles, K.H. (Innov Aging, 2017)
Decisions about who should be referred for post-acute care (PAC) are made by individual clinicians or teams for 14 million older adults per year, without national standards or guidelines. Using teams of multi-disciplinary experts we built a decision support (DS) tool that assists clinicians with these important decisions. The DS is based on two algorithms calculated from the characteristics of the patient during the hospital stay and provides a suggestion of refer or not, and which site of care is recommended. We will describe the development and testing of live DS in two hospitals. When the tool said to refer and patients did not get referred, readmission risk and ED use were 40% and 43% higher respectively, than those who did get referred. Use of DS can assure that high risk patients are identified and referred for PAC.